Study Of Secondary School Students\' Perceptions Of Learning History Through The Use Of Interactive Comic And Interactive Graphic Organizer - Tok Bee Lian, Jennie (2009)
The research aims to test the student\'s perception of the Interactive Graphic Organizer and Interactive Comic that the author personally developed against the conventional chalk and board method of the History teacher. Despite the many benefits and potential that both Graphic Organizer and Comics offer in the area of education, both media are rarely used and exploited by the teacher as an effective learning tool. By creating digital coursewares based on the two subjects and testing them against conventional learning, the author hopes to give an insight on the current situation of History lessons in Malaysia, and ways to improve the teaching and learning of History in Malaysia